2004
DOI: 10.1002/hed.20111
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated accelerated radiotherapy in combination with weekly cisplatin for locally advanced head and neck cancer

Abstract: HFRCB in combination with weekly cisplatin achieves a high rate of locoregional control and survival. Four weekly cycles of 40 mg/m2 cisplatin seem to be the dose limit for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 34 publications
9
51
2
2
Order By: Relevance
“…[38][39][40][41] Recent literature suggests that a combination of alternative fractionation with concomitant chemotherapy significantly improves results and could become the treatment of choice for locally advanced head and neck cancer. [42][43][44][45]54 Therefore, altered fractionation regimens remain an important topic of research.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] Recent literature suggests that a combination of alternative fractionation with concomitant chemotherapy significantly improves results and could become the treatment of choice for locally advanced head and neck cancer. [42][43][44][45]54 Therefore, altered fractionation regimens remain an important topic of research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the use of weekly low-dose CDDP plus RT for LASCCHN (11)(12)(13). Although there are no head-to-head randomized studies directly compared tri-weekly CDDP plus RT with weekly CDDP plus RT for LASCCHN, weekly CDDP plus RT seems to have less renal toxicity (Grade 3 or 4 in 0%) (11,13) and neurotoxicity (Grade 3 or 4 in 0-3%) (11,13) than tri-weekly CDDP plus RT (Grade 3 or 4 renal toxicity in 2-9%, Grade 3 or 4 neurotoxicity in 7%) (1,14,15). However, it is unclear whether weekly CDDP plus RT for our study population is safe or not.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improved survival and LRC compared to radiotherapy alone compliance with CRT regimens is suboptimal in many cases [1]. To limit toxicity, alternative schedules with reduced single doses of cisplatin have been established in HNSCC patients like 20 mg/m 2 d1-5 (week 1 and 5) [2,23], weekly 30 or 40 mg/m 2 [5,17] or even daily 6 mg/m 2 of cisplatin [18,26], but to date published data are comparably rare. Common to all schedules is the aim to achieve a cumulative cisplatin dose of at least 200 mg/m 2 (CisCD200), although the adequacy of this threshold dose remains to be proven.…”
Section: Introductionmentioning
confidence: 99%